Inhibitory activity of Australian culinary herb extracts against the bacterial triggers of selected autoimmune diseases - Edwin Cock, Ian; Maen, Anton (Pharmacognosy Communications)
High antioxidant capacities have been linked to the treatment of rheumatic diseases and in the inhibition of microbial growth. Recent reports have identified several native Australian culinary herbs with high antioxidant capacities. Despite this, several of these species are yet to be tested for the ability to inhibit the growth of the bacterial triggers of autoimmune inflammatory diseases. Methods: Solvent extracts prepared from selected Australian culinary herbs were analysed for antioxidant capacity by the DPPH free radical scavenging assay. Growth inhibitory activities against bacterial species associated with initiating rheumatoid arthritis and ankylosing spondylitis were determined by disc diffusion assay and quantified by MIC determination. Toxicity was determined by Artemia franciscana bioassay. Results: Methanolic extracts of most plant species displayed relatively high antioxidant contents (equivalent to approximately >10 mg of vitamin C per gram of fruit extracted). Most aqueous extracts also contained relatively high antioxidant capacities. The ethyl acetate and chloroform extracts generally had lower antioxidant capacities than the more polar extracts. In contrast, the hexane extracts of all species had low antioxidant contents (generally < 0.5 mg of vitamin C per gram of fruit extracted). Interestingly, the bacterial growth inhibitory activity of the extracts did not correlate with their antioxidant capacities. With the exception of native thyme, the herb extracts with the highest antioxidant capacities had only low antibacterial activity, with MIC values generally well in excess of 4000 µg/ml against all bacterial species. In contrast, many of the ethyl acetate extract and hexane extracts, which had low range antioxidant capacities (generally < 5 mg ascorbic acid equivalents/g extracted), had potent bacterial growth inhibitory activity with many MIC values substantially below 1000 µg/ml). The river mint ethyl acetate extract displayed toxicity in the Artemia franciscana bioassay (LC50=186 µg/mL). All other extracts were nontoxic. Conclusion: The lack of toxicity and inhibitory activity against microbial triggers of rheumatoid arthritis and ankylosing spondylitis by the Australian native culinary herb extracts indicates their potential in the treatment and prevention of these diseases.
Keywords: Ankylosing spondylitis; Functional foods; Native thyme; Native sage; Native basil; River mint; Rheumatoid arthritis; Wattle seed